KARAKTERISTIK DESAIN KURIKULUM HOMESCHOOLING TUNGGAL “SOLO HOMESCHOOLING” STUDI KASUS: SOLO HOMESCHOOLING SURAKARTA - Siti Shofiyatun; Septi Aprilia (SOKO GURU: Jurnal Ilmu Pendidikan, 2022)
In Solo, there are 4 families that have organized homeschooling, one of is Mr. Hidayat's family . Their children previously could not enjoy their study, after switching to homeschooling their children are happier when learning, critical, creative and have high curiosity. How is the curriculum design applied in single homeschooling "Solo Homeschooling" . The purpose of this study is to find out how the characteristics of the single homeschooling curriculum design "Solo Homeschooling". This study is qualitative research. Data was collected through interviews, observation and documentation. The data validity was obtained through data triangulation. The analytical used is an interactive analysis that consists of reduction and display data, then verification. The curriculum applied is correlated and integrated curriculum. Parents combine one subject to another, because the goal is not score but educational enlightenment, besides that it also integrates subject with problems that they see, hear and feel that are happening around them.